Respuesta :
Make use of the difference of squares identity,
[tex]a^2-b^2=(a-b)(a+b)[/tex]
Let [tex]a=\sqrt5-\sqrt7[/tex] and [tex]b=\sqrt{12}[/tex]. Then
[tex]\dfrac1{(\sqrt5-\sqrt7)+\sqrt{12}}\cdot\dfrac{(\sqrt5-\sqrt7)-\sqrt{12}}{(\sqrt5-\sqrt7)-\sqrt{12}}=\dfrac{(\sqrt5-\sqrt7)-\sqrt{12}}{(\sqrt5-\sqrt7)^2-(\sqrt{12})^2}=\dfrac{\sqrt5-\sqrt7-\sqrt{12}}{5-2\sqrt{35}+7-12}=-\dfrac{\sqrt5-\sqrt7-\sqrt{12}}{2\sqrt{35}}[/tex]
Now multiply the numerator and denominator by √(35):
[tex]-\dfrac{\sqrt5-\sqrt7-\sqrt{12}}{2\sqrt{35}}\cdot\dfrac{\sqrt{35}}{\sqrt{35}}=-\dfrac{(\sqrt5-\sqrt7-\sqrt{12})\sqrt{35}}{70}=-\dfrac{5\sqrt7-7\sqrt5-2\sqrt{105}}{70}[/tex]
Answer:
Multiply the numerator and denominator by the conjugate.
Exact Form:
1√5−√7+2√3
Decimal Form:
0.75267290…